2012
DOI: 10.1159/000335034
|View full text |Cite
|
Sign up to set email alerts
|

Experimentally Altered Navigational Demands Induce Changes in the Cortical Forebrain of Free-Ranging Northern Pacific Rattlesnakes <i>(Crotalus o. oreganus)</i>

Abstract: The hippocampus of birds and mammals plays a crucial role in spatial memory and navigation. The hippocampus exhibits plasticity in adulthood in response to diverse environmental factors associated with spatial demands placed on an animal. The medial and dorsal cortices of the telencephalon of squamate reptiles have been implicated as functional homologues to the hippocampus. This study sought to experimentally manipulate the navigational demands placed on free-ranging northern Pacific rattlesnakes (Crotalus o.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 81 publications
0
57
0
Order By: Relevance
“…There is a correlation, however, between relative medial cortex (medial pallium homologue) size and active predation, whereby medial cortex size is larger in active than in sit-and-wait lizards (63). In snakes, rattlesnakes forced to navigate after experimental displacement have an increased volume of medial, but not dorsal or lateral, cortex (64).…”
Section: Reptilesmentioning
confidence: 98%
“…There is a correlation, however, between relative medial cortex (medial pallium homologue) size and active predation, whereby medial cortex size is larger in active than in sit-and-wait lizards (63). In snakes, rattlesnakes forced to navigate after experimental displacement have an increased volume of medial, but not dorsal or lateral, cortex (64).…”
Section: Reptilesmentioning
confidence: 98%
“…Free-ranging northern Pacific rattlesnakes (Crotalus o. oreganus) that return to their home area after experimental displacements have larger MC relative to the dorsal cortex, compared with hand manipulated or undisturbed snakes [40]. Interspecific comparisons in closely related species of lizards have revealed that species with higher demands on spatial abilities have increased hippocampal volume.…”
Section: Medial Pallium or Hippocampus And Map-like Memories In Amniotesmentioning
confidence: 99%
“…In reptiles, the medial and dorsal cortices (MC and DC, respectively) are considered hippocampal homologues and similarly display plasticity with regards to spatial ecology. In male Northern Pacific rattlesnakes (Crotalus oreganus), short distance translocations caused increased home range size and an increase in MC volume (Holding et al, 2012). In male side-blotched lizards (Uta stainsburiana), non-territorial morphs had smaller DC volumes than morphs holding larger territories (LaDage et al, 2009).…”
Section: Introduction: Spatial Ecology and Cortical Brain Regionsmentioning
confidence: 99%
“…This increase in volume of these brain regions, or the hippocampus in mammals and birds, is mediated, at least in part, through increases in neurogenesis (Rats: Drapeau et al, 2003;Roof and Havens, 1992;Birds: LaDage et al, 2010). In reptiles, the medial and dorsal cortices (MC and DC, respectively) are considered hippocampal homologues and similarly display plasticity with regards to spatial ecology and territory or home range size (Holding et al, 2012;LaDage et al, 2009;Roth et al, 2006. Male cottonmouth snakes (Agkistrodon piscivorus) have larger MC compared to female conspecifics (Roth et al, 2006), presumably due to a sexual dimorphism in spatial movements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation